The Boy Without a Name - Shah, Idries 1924-1996.; Caron, Mona (Boston : Hoopoe Books, 2000)
A Sufi teaching tale of a boy without a name who visits a wise man and acquires both a name and a wonderful dream.
Accelerated Reader AR
Keywords: Sufi parables